Regional age structure and young workers' wages - Alfred Garloff; Duncan Roth (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
This paper estimates the effect that changes in the size of the youth population have on the wages of young workers. Assuming that differently aged workers are only imperfectly substitutable, economic theory predicts that individuals in larger age groups earn lower wages. We test this hypothesis for a sample of young, male, fulltime employees in Western Germany during the period 1999-2010. In contrast to other studies, functional rather than administrative spatial entities are used as they provide a more accurate measure of the youth population in an actual labour market. Based on instrumental variables estimation, we show that an increase in the youth share by one percentage point is predicted to decrease a young worker's wages by 3 %. Our results also suggest that a substantial part of this effect is due to members of larger age groups being more likely to be employed in lower-paying occupations. – – In diesem Papier werden die Auswirkungen untersucht, die Veränderungen in der Größe junger Altersgruppen auf die Löhne junger Arbeitnehmer haben. Unter der Annahme, dass Personen unterschiedlichen Alters nur unvollkommen substituierbar sind, besagt die ökomische Theorie, dass Personen in größeren Altersgruppen, ceteris paribus, niedrigere Löhne realisieren. Wir überprüfen diese Hypothese anhand eines Datensatzes, der junge, männliche Vollzeitbeschäftigte aus Westdeutschland in den Jahren 1999-2010 enthält. Im Gegensatz zu ähnlichen Untersuchungen werden allerdings funktionale statt administrativen räumlichen Einheiten verwendet, da diese die Bevölkerungsstrukturen innerhalb eines Arbeitsmarktes besser abbilden können. Unter Verwendung eines Instrumentvariablenansatzes zeigt sich, dass ein Anstieg im Anteil jüngerer Altersgruppen um 1 % zu einem Rückgang der Löhne junger Beschäftigter um etwa 3 % führt. Weiterhin legen die Ergebnisse nahe, dass ein beträchtlicher Teil dieses Effekts darauf zurückzuführen ist, dass Personen in größeren Altersgruppen eine höhere Wahrscheinlichkeit haben, in niedriger bezahlten Berufen zu arbeiten.
Keywords: J21; J31; R23; 330; age structure; wages; youth share; labour-market regions; instrumental variables; occupational selection